Coexistence of Familial Mediterranean Fever, Behçet’s Disease and Sacroiliitis - İsmihan SUNAR,; Zühre SARI SÜRMELİ,; Ali Erhan ÖZDEMİREL,; Ayşe Peyman YALÇIN,; Şebnem ATAMAN, (Archives of Rheumatology, 2015)
Familial Mediterranean fever is a genetic disorder restricted to certain ethnic groups and marked by acute attacks of serositis and the insidious development of amyloidosis. As well as arthritis, spondyloarthropathy may be encountered in the course of the disease. Vasculitis seems to be an important but not an adequately recognized feature of familial Mediterranean fever. In this article, we present a rare case of coexistence of familial Mediterranean fever, Behçet’s disease and sacroiliitis.